Secondary Metabolites And Antioxidant Activity Of Argania Spinosa (L.) Almonds Cultivated In The Three Region Of Morrocco (Journal of Namibian Studies : History Politics Culture, 2023)
Argania spinosa (L.) almond from tree region of Morocco have been analyzed for their secondary metabolites and antioxidant activities. The aim of this study was to determine the evolution of biometric parameters, antioxidant activity by DPPH (2, 2-diphenyl-1-picrylhydrazyl) free radical scavenging assay and hydrogen peroxide scavenging assay as well as total phenolic and flavonoid content of the argan almonds from three Moroccon regions (three argan plantation in the region of Casablanca, Dar Bouazza and Rhamna). Three characters were measured : weight, length and width of the argan almonds. The results showed that the almonds of the Dar Bouazza region presented the higher average width and weight and almonds of Rhamna had the highest average lenght. Total phenolic content extracted from almond using aqueous ethanol (40%, 60% and 80% ethanol) ranged from 12.18 to 48.27 mg GAE/g extract. The total flavonoid contents varied from 1.22 to 5.61 mg QE/g extract. Moreover, Antioxidant activity of different almond extracts from the three regions ranged from 48.35 and 77.43 μg/mL. The results showed that the ethanol extract of 40% from Dar Bouazza region, showed the highest phenolic (42.27mg GAE/g) and flavonoid (5.61 mg GAE/g) content and strong antioxidant and hydrogen peroxide scavenging activity. These results suggest that Argania spinosa (L.) almond extracts from the three regions could be used as natural plant sources of antioxidants.